Comparing Health-Related Quality of Life of Cancer Patients under Chemotherapy and of Their Caregivers - Ioannis Vrettos; Konstantinos Kamposioras; Nick Kontodimopoulos; Evelina Pappa; Elissavet Georgiadou; Dionysios Haritos; Angelos A. Papadopoulos; Dimitris Niakas (The Scientific World Journal)
Introduction. Cancer is a major disorder physically and psychologically affecting both patients and their caregivers. In this study, health-related quality of life (HRQoL) of patient-caregiver dyads during the period of chemotherapy was assessed. Material and Methods. Two hundred twenty-two cancer patient-caregiver dyads were enrolled in the study, which was conducted from October 2008 to March 2009. HRQoL was evaluated with EQ-5D. Results. The mean age of the sample was 57.4 and 48.9 for patients and caregivers, respectively. The EQ-5D descriptive system indicates that female patients more frequently experience anxiety and depression than male patients. Male and higher-education caregivers had higher VAS scores, while demographic factors did not seem to influence patients’ HRQoL. Anxiety and depression of caregivers were correlated with patients’ problems in self-care and usual activities. Conclusions. Quality of life is highly influenced during the period of chemotherapy for both patients and caregivers and is often under reported. Interventions that can improve HRQoL, especially in the domain of mental health for both cancer patients and their caregivers, need to be implemented.